Comparisons of Differentiation Potential in Human Mesenchymal Stem Cells from Wharton’s Jelly, Bone Marrow, and Pancreatic Tissues - Shih-Yi Kao; Jia-Fwu Shyu; Hwai-Shi Wang; Chi-Hung Lin; Cheng-Hsi Su; Tien-Hua Chen; Zen-Chung Weng; Pei-Jiun Tsai (Stem Cells International)
Background. Type 1 diabetes mellitus results from autoimmune destruction of β-cells. Insulin-producing cells (IPCs) differentiated from mesenchymal stem cells (MSCs) in human tissues decrease blood glucose levels and improve survival in diabetic rats. We compared the differential ability and the curative effect of IPCs from three types of human tissue to determine the ideal source of cell therapy for diabetes. Methods. We induced MSCs from Wharton’s jelly (WJ), bone marrow (BM), and surgically resected pancreatic tissue to differentiate into IPCs. The in vitro differential function of these IPCs was compared by insulin-to-DNA ratios and C-peptide levels after glucose challenge. In vivo curative effects of IPCs transplanted into diabetic rats were monitored by weekly blood glucose measurement. Results. WJ-MSCs showed better proliferation and differentiation potential than pancreatic MSCs and BM-MSCs. In vivo, WJ-IPCs significantly reduced blood glucose levels at first week after transplantation and maintained significant decrease till week 8. BM-IPCs reduced blood glucose levels at first week but gradually increased since week 3. In resected pancreas-IPCs group, blood glucose levels were significantly reduced till two weeks after transplantation and gradually increased since week 4. Conclusion. WJ-MSCs are the most promising stem cell source for β-cell regeneration in diabetes treatment.